2008
DOI: 10.1002/tox.20427
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aroclor 1254 on benzo(a)pyrene‐induced DNA breakage, oxidative DNA damage, and cytochrome P4501A activity in human hepatoma cell line

Abstract: Both polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) are important environmental pollutants. They coexist widely in the environment at very low levels. Numerous studies indicated that aroclor1254 (one of PCBs mixture) is the inducer of cytochrome P450 1A enzyme acitivity. Benzo(a)pyrene (BaP) can cause a variety of toxicities in vitro, such as oxidative DNA damage and genotoxicity. In the present study, HepG2 cells were treated with either BaP (50 microM) or aroclor1254 at concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“…Furthermore, TCS treatment promoted the accumulation of 8-OHdG in the genomic DNA, but reduced the relative levels of MBD2, MBD3, and MeCP2 mRNA transcripts in HepG2 cells. We used HPLC-MS/MS for quantification of the levels of GDM and 8-OHdG and found that the levels of GDM and 8-OHdG in un-treated HepG2 cells were similar to that in other reports Aniagu et al, 2009;Yuan et al, 2009), validating the sensitivity of our experimetnal system. Furthermore, treatment with a DNA methylation inhibitor of AZA greatly decreased the GDM level, while treatment with NAC significantly mitigated TCS-induced accumulation of 8-OHdG in genomic DNA, both of which further validated the accuracy of this method.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, TCS treatment promoted the accumulation of 8-OHdG in the genomic DNA, but reduced the relative levels of MBD2, MBD3, and MeCP2 mRNA transcripts in HepG2 cells. We used HPLC-MS/MS for quantification of the levels of GDM and 8-OHdG and found that the levels of GDM and 8-OHdG in un-treated HepG2 cells were similar to that in other reports Aniagu et al, 2009;Yuan et al, 2009), validating the sensitivity of our experimetnal system. Furthermore, treatment with a DNA methylation inhibitor of AZA greatly decreased the GDM level, while treatment with NAC significantly mitigated TCS-induced accumulation of 8-OHdG in genomic DNA, both of which further validated the accuracy of this method.…”
Section: Discussionsupporting
confidence: 63%
“…E) The structures of TCS and MTCS. Control cells were treated with 0.1% DMSO (v/v) level of 8-OHdG levels in HepG2 cells was 2.3/10 6 dG, which was similar to the reported data by Yuan et al (2009). After treated with low-dose TCS, 8-OHdG levels significantly increased (p b 0.01) compared with the control group (Fig.…”
Section: Effects Of Low-dose Tcs On 8-ohdg Levels After Exposure For supporting
confidence: 88%
“…PCBs enhanced CYP450 activities in animals [21, 22]. By MTT and Western blot methods, our results proved that the expression of CYP450 increased gradually with the treatment of the gradient Aroclor 1254; the highest expression was observed under 1  μ g/mL Aroclor 1254 treatment.…”
Section: Discussionmentioning
confidence: 66%